Aberrant White Matter Microstructure in Depressed Patients with Suicidality. Issue 4 (22nd September 2021) - Zhang, Huawei; Li, Huiru; Yin, Li; Chen, Ziqi; Wu, Baolin; Huang, Xiaoqi; Jia, Zhiyun; Gong, Qiyong
Abstract : Background: Depression is a common psychiatric disorder affecting 264 million people globally, and the worst outcome is suicide. While regional brain alterations in depressed suicidal brain have previously been reported, knowledge about white matter (WM) microstructure is limited. Purpose: Automated fiber quantification (AFQ) acquired by magnetic resonance imaging was used to calculate diffusion properties of fiber tracks to explore the structural alteration of WM associated with suicidality in depressive patients. Study Type: Cross‐sectional. Subjects: Forty‐five depressive patients without suicidality (DS− group, 60.00% females), 53 depressed patients with suicidality (DS+ group, 66.04% females), and 59 healthy controls (HC group, 67.80% females). Field Strength/Sequence: 3.0 T; single‐shot echo‐planar imaging sequence. Assessment: The point‐wise group difference of the fiber tracts was determined by diffusion properties including fractional anisotropy, mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) of 18 specific WM tracts. Statistical Tests: Analysis of covariance (ANCOVA) and partial correlation analysis were used. A threshold of P < 0.05 was considered statistically significant. Results: The significantly different diffusion properties were found in callosum forceps, left inferior fronto‐occipital fasciculus (IFOF), right anterior thalamic radiation (ATR), and left cingulum cingulate in DS− and DS+ groups. The correlation analysis results showed that MD of right ATR was significantly positively correlated with Hamilton Depression Rating Scale (HAMD) scores ( r = 0.363). In addition, AD of right ATR ( r = 0.372), MD of callosum forceps minor ( r = 0.511), RD of left IFOF ( r = 0.429), and RD of callosum forceps minor ( r = 0.515) were significantly positively correlated with suicide item scores of HAMD. Data Conclusion: Our demonstration of decreased WM tract integrity including callosum forceps, IFOF, and ATR confirms the central involvement of the frontal cortex and limbic system with suicidality in depression. Level of Evidence: 3 Technical Efficacy Stage: 3